Demographic and socioeconomic impact of water, sanitation, and hygiene in occurrence of diarrheal disease among pediatric age group in Abia state - Ohanenye, Chioma A; Amadi, Chinasa Orie; Ede, Okorie Alison; Offiah, Awa Ukony; Nkwa, Amadi Agwu; Iro, Okechukwu; Nwazunku, Augustine A; Okoronkwo, Nneka Chioma (Indian Journal of Child Health, 2020)
Background: Potable water, good sanitary conditions, and good hygienic practices are essential for the survival and development of children. Objective: The study aimed to determine the demographic and socioeconomic effect of water, sanitation, and hygiene (WASH) in the occurrence of diarrheal disease among pediatric age group in Aba, Abia State. Materials and Methods: The study adopted a descriptive cross-sectional survey design to assess the environmental sanitation in the selected study areas. The survey was designed with the use of questionnaire which was administered to a sample size of 360 participants. The collected data were entered into computer software called Statistical Package for the Social Sciences (SPSS) Version 20.0 and analyzed using descriptive statistical analysis. Results: The results were displayed in frequency tables and charts. The relation between variables was determined with Fisher’s exact test and the findings showed that 267 (74.1%) of the participants reported with 1–5 times episodes of diarrhea/year and 204 (56.7%) participants had available water supply and the major source of water supply was borehole in 227 (63.1%) participants. In terms of water treatment, 255 (70.8%) reported of not boiling water before use; 100 (27.7%) did not wash hands after defecation, 225 (62.5%) did not wash hands after touching pet animals, and only 32 (8.8%) reported of not washing fruits/vegetables before eating or cooking. A total of 264 (73.3%) had the knowledge of treating children with diarrhea at health center. Conclusion: WASH had impact in the occurrence of diarrheal disease among pediatric age group in relation to demographic and socioeconomic factors. However, the available and functional sanitary facilities do not meet the required standards. Therefore, awareness should be generated on the importance of WASH practices in all local governments in Abia State.